Rho-dependent kinase is involved in agonist-activated calcium entry in rat arteries - Ghisdal, Philippe (Blackwell Science Inc, 2003)
The present study was aimed at investigating whether, besides its pivotal role in Ca(2+)-independent contraction of smooth muscle, Rho-kinase is involved in the mechanisms underlying the Ca(2+) signal activated by noradrenaline in arteries. In rat aorta and mesenteric artery, the Rho-kinase inhibitor Y-27632 (10 μM) completely relaxed the contraction evoked by noradrenaline (1 μM) and simultaneously inhibited the Ca(2+) signal by 54 ± 1 % (mesenteric artery) and 71 ± 15 % (aorta), and the cell membrane depolarisation by 56 ± 11 % (mesenteric artery). A similar effect was observed in arteries contracted by AlF(4)(−), while in KCl-contracted arteries, Y-27632 decreased tension without changing cytosolic Ca(2+). The same effects were observed with another inhibitor of Rho-kinase (HA1077) but not with an inhibitor of protein kinase C (Ro-31–8220). Effects of Y-27632 were not prevented by incubating the artery in 25 mM KCl, with K(+) channel blockers or with the Ca(2+) channel blocker nimodipine. Y-27632 did not affect either the increase in the production of inositol phosphates activated by noradrenaline, or the release of Ca(2+) from non-mitochondrial stores evoked by InsP(3) in permeabilised aortic cells, or the Ca(2+) signals evoked by thapsigargin or caffeine. The capacitative Ca(2+) entry activated by thapsigargin was not impaired by Y-27632, but the entry of Ba(2+) activated by noradrenaline in the presence of nimodipine was blocked by 10 μM Y-27632. These results indicate that Rho-kinase is involved in noradrenaline activation of a Ca(2+) entry distinct from voltage- or store-operated channels in rat arteries.